Therapeutic storytelling for adolescents and young adults - Slivinske, Johanna (Oxford University Press, 2014)
Adolescents are often an overlooked clinical population. Among school-based practitioners, there is a natural inclination to focus the delivery of mental health services, assessment measures, and intervention plans on younger children, and there is a strong research base to support these programs. On the other hand, the waiting rooms of most practitioners in private practice are filled with young and middle-age adults, couples, or families with young children. Because most therapists do not specialize in working with teens, who might make up only a small portion of their overall caseload, ther.